EXPLORING THE NEXUS BETWEEN FINANCIAL INCLUSION AND POVERTY ALLEVIATION AMONG WOMEN SMALL BUSINESS OWNERS - Kamaldeen Ibraheem Nageri (Fakultas Ekonomi Universitas Islam Darul Ulum Lamongan, 2024)
In today’s fast-evolving world, financial inclusion is a central aspect of financial innovation, making it a significant driver of financial inclusion. It remains a key concept in development policy because it plays a crucial role in reducing extreme poverty and fostering inclusive growth and development. This study investigates the effect of financial inclusion on poverty reduction among women small business owners. The paper utilizes correlation analysis and the binary logit regression technique to show the evidence based on selected samples in Tarauni Local Government, Kano State, Nigeria. The result revealed a negative yet significant association between financial inclusion and poverty alleviation. This is due to the high cost of financial services and poor financial literacy. Also, gender inequality has revealed a positive and significant relationship. Women have been deprived of certain opportunities and benefits due to cultural and social barriers. The findings call for further inquiry into the significant factors that that influence how financial inclusion impact poverty alleviation among women small business owners. The paper offers that the government should invest in financial education to promote responsible financial product use. Because some people have access to financial services but do not know how to use them efficiently. Moreso, financial institutions should be saddled with the responsibility of developing financial services specifically for low-income persons, such as micro-loans with lower interest rates and flexible repayment schedules.